2017
DOI: 10.1163/15691330-12341414
|View full text |Cite
|
Sign up to set email alerts
|

Countries versus Disciplines: Comparative Analysis of Post-Soviet Transformations in Academic Publications from Belarus, Russia and Ukraine

Abstract: The objective of this paper is to outline and compare frameworks for studying post-Soviet transformations developed by social scientists from various disciplines in Belarus, Russia and Ukraine. The objective is realized by means of quantitative content analysis of scholarly articles’ abstracts in ninety-four journals in eight (inter)disciplinary fields that covers the period of 2001-2015. This paper seeks to answer the question whether differences in the studies of the post-Soviet transformations are defined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[19,20], the characteristics of the disciplinary structure at the country level has been investigated in many studies [21][22][23][24][25][26][27][28][29][30]. The analysis of the disciplinary profiles of Eastern Europe contries and Soviet Union and its evolution after the breakup of the Soviet Union has been the subject of several studies [31][32][33][34][35]. Harzing and Giroud [23] comparing the profiles of 34 countries across 21 disciplines showed that nations with the fastest increase in their scientific productivity during the periods 1994-2004 and 2002-2012, which tidied up their disciplinary profile towards a more uniform one, then continued relatively unchanging in their wellproportioned disciplinary structures.…”
Section: Databases and Observablesmentioning
confidence: 99%
“…[19,20], the characteristics of the disciplinary structure at the country level has been investigated in many studies [21][22][23][24][25][26][27][28][29][30]. The analysis of the disciplinary profiles of Eastern Europe contries and Soviet Union and its evolution after the breakup of the Soviet Union has been the subject of several studies [31][32][33][34][35]. Harzing and Giroud [23] comparing the profiles of 34 countries across 21 disciplines showed that nations with the fastest increase in their scientific productivity during the periods 1994-2004 and 2002-2012, which tidied up their disciplinary profile towards a more uniform one, then continued relatively unchanging in their wellproportioned disciplinary structures.…”
Section: Databases and Observablesmentioning
confidence: 99%
“…It was noticed that characteristics of the disciplinary structure may also be a factor that affects the competitive advantages of national sciences (Yang et al, 2012 ; Bongioanni et al, 2014 , 2015 ; Cimini et al, 2014 ; Harzing and Giroud, 2014 ; Radosevic and Yoruk, 2014 ; Albarran et al, 2015 ; Lorca and de Andrés, 2019 ; Pinto and Teixeira, 2020 ). For example, it has been argued that this archaic disciplinary structure is one of the reasons why Russia and other former communist countries are still lagging behind Western nations (Kozlowski et al, 1999 ; Markusova et al, 2009 ; Adams and King, 2010 ; Guskov et al, 2016 ; Jurajda et al, 2017 ; Tregubova et al, 2017 ; Shashnov and Kotsemir, 2018 ). In a comprehensive study of how disciplinary structure is related to the competitive advantage in science of different nations, Harzing and Giroud ( 2014 ) showed that countries that demonstrated the fastest increase in their scientific productivity during the periods 1994–2004 and 2002–2012 remained relatively stable in their fairly well-balanced disciplinary structures.…”
Section: The Scientific Impact Derived From the Disciplinary Profilesmentioning
confidence: 99%